2008
DOI: 10.1104/pp.108.116764
|View full text |Cite
|
Sign up to set email alerts
|

The “Old” Euonymus europaeus Agglutinin Represents a Novel Family of Ubiquitous Plant Proteins    

Abstract: Molecular cloning of the “old” but still unclassified Euonymus europaeus agglutinin (EEA) demonstrated that the lectin is a homodimeric protein composed of 152 residue subunits. Analysis of the deduced sequence indicated that EEA is synthesized without a signal peptide and undergoes no posttranslational processing apart from the removal of a six-residue N-terminal peptide. Glycan array screening confirmed the previously reported high reactivity of EEA toward blood group B oligosaccharides but also revealed bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 19 publications
0
43
0
1
Order By: Relevance
“…We can safely conclude that the dramatically elevated Ca 2+ concentrations in the cytoplasm correlated well with the strong down-regulation of calreticulins (spots 1 and 48). In addition, the newly identified Hyp-rich glycoprotein (spot E17) is a stressresponsive lectin-like protein that contains a QXW lectin repeat domain, which might be a first step in the recognition of the involvement and importance of proteinglycoconjugate interactions in some essential cellular processes Fouquaert et al, 2008).…”
Section: Signaling Proteins As the Pleiotropic Responsesmentioning
confidence: 99%
“…We can safely conclude that the dramatically elevated Ca 2+ concentrations in the cytoplasm correlated well with the strong down-regulation of calreticulins (spots 1 and 48). In addition, the newly identified Hyp-rich glycoprotein (spot E17) is a stressresponsive lectin-like protein that contains a QXW lectin repeat domain, which might be a first step in the recognition of the involvement and importance of proteinglycoconjugate interactions in some essential cellular processes Fouquaert et al, 2008).…”
Section: Signaling Proteins As the Pleiotropic Responsesmentioning
confidence: 99%
“…Of particular interest are the Euonymus lectin sequences, which are present in all sequenced genomes. The Euonymus europaeus agglutinin (EEA) was cloned a few years ago (Fouquaert et al, 2008). As then EEA has become the prototype of a new family of proteins referred to as the Euonymus lectin-related (EUL) family, grouping all proteins with one or more EUL-related sequences.…”
Section: Introductionmentioning
confidence: 99%
“…As then EEA has become the prototype of a new family of proteins referred to as the Euonymus lectin-related (EUL) family, grouping all proteins with one or more EUL-related sequences. In silico screening of available genomes and transcriptomes revealed that the EUL family is omnipresent in the plant kingdom (Fouquaert et al, 2008). Based on the architecture of the EUL domain identified in different protein sequences, a classification system was elaborated (Fouquaert et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 the molecular cloning of the Euonymus europaeus agglutinin (EEA) from spindle tree led to the discovery of a new family of lectins [3]. Since then the Euonymus lectin domain (EUL) is considered as the structural unit of a novel family of putative carbohydrate-binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive screening of publicly accessible genome databases revealed that the EUL domain is widespread among green plants [3]. Furthermore some sequences consist of a single EUL domain linked to an unrelated N-terminal domain whereas others comprise two in tandem arrayed EUL domains.…”
Section: Introductionmentioning
confidence: 99%